2020
DOI: 10.1093/eurheartj/ehaa381
|View full text |Cite
|
Sign up to set email alerts
|

EAPCI Position Statement on Invasive Management of Acute Coronary Syndromes during the COVID-19 pandemic

Abstract: The coronavirus disease 2019 (COVID-19) pandemic poses an unprecedented challenge to healthcare worldwide. The infection can be life threatening and require intensive care treatment. The transmission of the disease poses a risk to both patients and healthcare workers. The number of patients requiring hospital admission and intensive care may overwhelm health systems and negatively affect standard care for patients presenting with conditions needing emergency interventions. This position statements aims to assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
128
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(134 citation statements)
references
References 43 publications
0
128
0
6
Order By: Relevance
“…The vast majority of ACS patients are candidates for medical treatment based on clinical risk, and only very high-risk Non-STEMI cases and STEMI patients require taking an interventional approach. 6 Our statistics related to incidence of STEMI are mostly in the form of case reports, and therefore, the epidemiology cannot be stated precisely. During a 40-day study in Lombardy, Italy, from February 20 to March 30, 28 cases of STEMI were reported, 24 of which (85.7%) reported STEMI as the first manifestation of COVID-19 before polymerase chain reaction (PCR) testing.…”
Section: Basic Concepts and Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations
“…The vast majority of ACS patients are candidates for medical treatment based on clinical risk, and only very high-risk Non-STEMI cases and STEMI patients require taking an interventional approach. 6 Our statistics related to incidence of STEMI are mostly in the form of case reports, and therefore, the epidemiology cannot be stated precisely. During a 40-day study in Lombardy, Italy, from February 20 to March 30, 28 cases of STEMI were reported, 24 of which (85.7%) reported STEMI as the first manifestation of COVID-19 before polymerase chain reaction (PCR) testing.…”
Section: Basic Concepts and Epidemiologymentioning
confidence: 99%
“…Additionally, echocardiography can also be helpful in assessing regional wall motion abnormality in suspected cases. 6 Recent reports have shown an increase in cardiac biomarkers such as troponin from 5% to 25% in patients with COVID-19 who are in intensive care unit. 2 , 14 In fact, this increase is due to acute myocardial injury and is associated with a worse prognosis in patients.…”
Section: Diagnostic Approach For Covid-19 Patients and Stemimentioning
confidence: 99%
See 2 more Smart Citations
“…A recent European position statement on invasive management of ACS during the COVID-19 pandemic emphasised that the use of coronary angiography for COVID-19-positive patients with elevation in troponin-c should be restricted to those in whom type I ACS is suspected. 30 This occurs more often in men than women and its diagnosis may be delayed in people needing longterm ventilation. 31 In the Lombardy region, a striking increase in out-of-hospital cardiac arrests of 58% was seen compared to a year earlier, of which more than 77% were related to COVID19 infections.…”
Section: Sex Differences In Cardiac Manifestations Of Covid-19mentioning
confidence: 99%